Peran Etika Pemerintahan Sebagai Upaya Dalam Pengentasan Korupsi di Masa Pandemi Covid 19 di Desa Cinta Damai - Ade Khairun Nisa; Baskoro Wicaksono (Universitas Indo Global Mandiri, 2022)
The purpose of this research is to see how the role of government ethics as an effort to eradicate corruption during the COVID-19 pandemic in the peace-loving village. By using descriptive qualitative research methods, the supporting data obtained are LKPJ data from 2020 to 2021 and information mining is carried out by interviewing the village secretary, village officials and several informants from the peace-loving village community. This research was carried out for 14 days, starting from November 1-14, 2021. The results of this study were that as long as the observations from researchers of corruption in the peace-loving village did not occur, the peace-loving village government had carried out several government ethical tips in every activity during the covid 19 pandemic. The village government has also made various efforts to reduce the space for corruption, including implementing anti-corruption education, in this case the peace-loving village government has provided a banner containing extortion and the authority of the Direct Cash Assistance (BLT) service to the community. socialization to the community that there is no money as a token of gratitude or tips for village officials in providing any services, setting SOP in services, implementing E-services, and accommodating the complaint service center so that the community can complain if there are fraud and acts of corruption committed by village officials In addition, it aims to improve government services to the community. Keywords: Role, Government Ethics, Corruption, and Covid19